STRATEGI PEMASARAN DIGITAL DAN UMKM DAN KAITANNYA DENGAN PENGANGGARAN BIAYA PROMOSI: STUDI KASUS PADA “FLOTA COFFE - Rita J D Atarwaman; Bulandari, Jihan Sartika; Mahu, Sundusin; mbulex, Marsyah; sangadji, Alvira aprilyana; Maitimu, Wihel; Supit, Chesya; sipahelut, Paunelin florensia; lawalata, , Marcellino; Resley, Helita; limasana, Orlando; da Costa, Michel angelo; Pelupessy, Arleston (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to analyze the digital marketing strategy implemented by Micro, Small, and Medium Enterprises (Flota coffee) and its relationship to promotional budgeting. The case study was conducted at Flota Coffee which is trying to increase market reach through digital platforms. In the era of rapid digitalization, the use of social media, e-commerce, and content strategies are important parts in increasing Flota Coffee's competitiveness. This study uses a qualitative approach with a case study method, through direct observation and in-depth interviews with business actors. The results of the study indicate that a well-planned digital marketing strategy can have a significant impact on the effectiveness of promotion, even with a limited budget. In addition, it was found that allocating a proportional promotional budget to digital media can increase the visibility and sales of Flota Coffee products. The implications of this study show the importance of strategic budget planning in digital marketing activities to support the sustainability and growth of Flota Coffee in the digital era.